Anteroposterior Cannulated Screw Fixation of Coronoid Fractures in Terrible Triad Injuries: A Simple Syringe‐guided Technique. Issue 10 (5th September 2022) - Cooper, Tokai B.; Luo, Xiaobin; Chen, Yiheng; Chen, Xinglong; Yan, Hede; Zhou, Feiya
Abstract : Objective: The fixation of the coronoid fractures in terrible triad injuries is quite challenging. In this study, we introduce a minimally invasive technique using a syringe as a guide for insertion of the cannulated screw in an anterior to posterior fashion to fix the coronoid fracture in patients with terrible triad injuries. Methods: In this retrospective study, clinical data of patients suffering from terrible triad injuries between 2012 and 2019 were analyzed. Fifteen patients with an average age of 38.2 years old (21–56 years) were enrolled in this study, of which 12 were males and three were females. The Regan–Morrey type II and type III coronoid fractures in these patients were treated with cannulated screws, inserted anteriorly using a 1 mL syringe as a guide. Outcome measures included pain, range of motion, stability and daily function using Mayo Elbow Performance scores (MEPs). The anteroposterior and lateral radiographs were used for evaluating a healing fracture. Results: After a mean follow up of 44.2 months (range 13–80), the mean elbow flexion was 128.2°, extension was 12.3°, forearm pronation was 74.6° and supination was 73.6°. A concentric reduction was maintained without severe pain, stiffness, and radiographic evidence of instability in all patients during the follow‐up period. The mean MEPs was 89.7 points. Conclusion: The anteroposterior cannulated screw fixation via simple syringe guide is a minimally invasive and safe option for surgical treatment of coronoid fractures in terrible triad injuries. Abstract : Minimally invasive anterior approach and a direct lateral approach to address the fractured coronoid. Avoiding further injury to important anterior soft tissues. Allowing adequate lateral view of the fractured coronoid and a concentric anterior fixation. BA, brachial artery; BT, biceps tendon; CFL, coronoid fracture line; MN, median nerve; GW, guide wire.